Potresni odziv vodoravnih betonskih fasadnih sistemov armiranobetonskih montažnih stavb - Starešinič, Gabrijela (visokošolska dela, 2021)
The seismic performance of prefabricated, reinforced concrete (RC) structures with horizontal concrete façade systems typically used across Central Europe was investigated. Extensive static and dynamic experiments supported analytical and numerical research presented in the dissertation. Many tests were successfully simulated by newly defined numerical models. A basic in-plane response mechanism of the fastening system consists of three distinct stages: sliding with limited friction, contact with the panel causing an increase in stiffness of the connection and brittle failure. The top connections are the weakest components of the fastening system. Experimental observations during the shake table tests and extensive parametric study showed that the column drift along the single panel could measure capacity and demand on the fastening system. Various important parameters and their influence on the seismic response were analysed. The initial position of cladding connections significantly influences the responses and the drift capacity of the system. Thus, a proposal was made in the dissertation to improve the façade system based on providing more space for connections to slide. The influence of the façade system on the response of the main structure is small. It can be noticed only for very slender structures with small tributary mass. The response of the main precast structure could be reasonably well estimated with a current design approach. A relatively simple procedure for estimating the approximate demand on the façade system is given. At the end of the thesis, a numerical analysis and evaluation of a restrainer system were performed.
Keywords: Armiranobetonske konstrukcije; armiranobetonske montažne stavbe; Built environment; connections; Disertacije; doctoral thesis; Grajeno okolje; horizontal façade system; mehanizem odziva; numerical modelling; numerično modeliranje; parametric study; parametrična študija; Potresna varnost; potresni odziv; reinforced concrete precast buildings; response mechanism; seismic response; stiki; vodoravni fasadni sistem